Pollinator monitoring more than pays for itself. Issue 1 (7th October 2020) - Breeze, Tom D.; Bailey, Alison P.; Balcombe, Kelvin G.; Brereton, Tom; Comont, Richard; Edwards, Mike; Garratt, Michael P.; Harvey, Martin; Hawes, Cathy; Isaac, Nick; Jitlal, Mark; Jones, Catherine M.; et al.
Abstract: Resilient pollination services depend on sufficient abundance of pollinating insects over time. Currently, however, most knowledge about the status and trends of pollinators is based on changes in pollinator species richness and distribution only. Systematic, long‐term monitoring of pollinators is urgently needed to provide baseline information on their status, to identify the drivers of declines and to inform suitable response measures. Power analysis was used to determine the number of sites required to detect a 30% change in pollinator populations over 10 years. We then evaluated the full economic costs of implementing four national monitoring schemes in the UK: (a) professional pollinator monitoring, (b) professional pollination service monitoring, (c) volunteer collected pan traps and (d) volunteer focal floral observations. These costs were compared to (a) the costs of implementing separate, expert‐designed research and monitoring networks and (b) the economic benefits of pollination services threatened by pollinator loss. Estimated scheme costs ranged from £6, 159/year for a 75‐site volunteer focal flower observation scheme to £2.7 M/year for an 800‐site professional pollination service monitoring network. The estimated research costs saved using the site network as research infrastructure range from £1.46–4.17 M/year. The economic value of UK crop yield lost following a 30% decline in pollinators was estimated at ~£188 M/year. Synthesis and applications . We evaluated the full costs of running pollinator monitoring schemes against the economic benefits to research and society they provide. The annual costs of monitoring are <0.02% of the economic value of pollination services that would be lost after a 30% decline in pollination services. Furthermore, by providing high‐quality scientific data, monitoring schemes would save at least £1.5 on data collection per £1 spent. Our findings demonstrate that long‐term systematic monitoring can be a cost‐effective tool for both answering key research questions and setting action points for policymakers. Careful consideration must be given to scheme design, the logistics of national‐scale implementation and resulting data quality when selecting the most appropriate combination of surveyors, methods and site networks to deliver a successful scheme. Abstract : We evaluated the full costs of running pollinator monitoring schemes against the economic benefits to research and society they provide. The annual costs of monitoring are <0.02% of the economic value of pollination services that would be lost after a 30% decline in pollination services. Furthermore, by providing high‐quality scientific data, monitoring schemes would save at least £1.5 on data collection per £1 spent. Our findings demonstrate that long‐term systematic monitoring can be a cost‐effective tool for both answering key research questions and setting action points for policymakers. Careful consideration must be given to scheme design, the logistics of national‐scale implementation and resulting data quality when selecting the most appropriate combination of surveyors, methods and site networks to deliver a successful scheme. 摘要: 弹性授粉服务取决于久而久之授粉昆虫量的足够充裕。然而目前大量关于授粉者状态和动态的知识仅以授粉者物种种类与其分布为基础。 系统来说, 对授粉者的长期监控急需针对其状态而提供的基准信息, 以此识别衰退的驱动原因并报告合适的应对措施。 功率分析用以确定所需地点的数量, 以此探测10年中授粉者数量的30%变化。随后, 我们评估了在英国实行四种全国性监控方案所需的完全经济成本: (1) 专业授粉者监控。 (2) 专业授粉服务监控。 (3) 志愿者收集陷阱盘。 (4) 志愿者花朵观察。这些成本的比较来源: (1) 实施分离的、专家设计的研究和监控网络的成本。 (2) 受授粉者减少而威胁的授粉服务经济利益。 预测方案成本范围从 6, 159英镑/年（75地志愿者花朵观察方案） 至270万英镑/年（800地专业授粉服务监控网络）。预测研究成本通过使用地点网络作为研究基建的范围为146万英镑至417万英镑/年。由授粉者数量30%的下降而导致的英国作物产量损失预测为 1.88亿英镑/年左右。 综合与应用。我们与方案所提供的、针对研究与社会的经济利益相比, 评估了运作授粉者监控方案的完整成本。监控的年度成本与授粉服务经30%衰退后的经济价值相比, 小于等于0.02%。此外, 通过提供高质量科学数据, 监控方案在数据收集上能在每1英镑成本上节省至少1. 5英镑。我们的调查结果证明长期的系统监控能作为高成本有效的工具, 为答复关键研究问题和为决策者制定行动点服务。在选择最为合适的测量员、方法和地点网络时, 应对方案设计、全国性后勤实施和产生的数据质量给予慎重考虑, 以此交付最成功的方案。